Determination of the ursolic and oleanolic acids content with the antioxidant capacity in apple peel extract of various cultivars - F. Odun-Ayo; K. Chetty; L. Reddy (Brazilian Journal of Biology, 2022)
Abstract Apples are rich sources of ursolic acid (UA) and oleanolic acid (OA) which are the major and most prominent triterpenes in the peel of an apple. Pentacyclic triterpenes are ideal nutraceuticals due to their ability to reduce the risk of many life-threatening diseases such as cancer, cardiovascular and diabetes. This study was to determine the content of UA and OA in the apple peel extract from different cultivars grown in South Africa as well as the correlation of their content level with antioxidant capacity. Quantitative analysis of UA and OA in apple peels from three cultivars; red delicious (RD), royal gala (RG) and granny smith (GS) apples was carried out using HPLC and their antioxidant capacity was analyzed using the DPPH assay. The RD showed the highest content of UA and OA (248.02 ± 0.08 µg/ml and 110.00 ± 0.08 µg/ml respectively) in the apple peel extract and also displayed a significantly high level of antioxidant capacity (97.3 ± 0.40%; p < 0.0001) compared to the RG and GS cultivars. A strong positive correlation was noted between the UA, OA and antioxidant capacities of all the cultivars. Only the RD cultivar showed a significant correlation though; UA (r = 0.9570; p = 0.0027) and OA (r = 0.8503; p = 0.0319). This study demonstrated that the RD and RG apple peels possess the highest UA and OA content which invariably increases their antioxidant activities compared to GS apple. Thus, both apple cultivars would be useful and recommended for food consumption and nutraceuticals values to improve human health.